(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Water is one of the most necessary physiological needs of humans. Water is called the universal solvent because more substances dissolve in water than in any other chemical. Water is generally used for cleaning, cooking, bathing, and drinking or so-called “panulak” by many. Given the importance of water to human’s daily lives, researchers think of a business that is suited to their primary needs. The purpose of A-Healing Water is to serve clean and safe water to household users and other individuals, especially to those people who are not able to acquire filtered water and drink directly to the faucet, which occasionally results in minor health issues such as diarrhea. Hence, researchers made the price of their products available and affordable to these individuals. The researchers used qualitative analysis. To conduct a survey, questionnaires were given to respondents to determine if this business will grow in the location of the business in the future. The respondents of this study were composed of 31 residents and 19 students, with a total of 50 persons. The results of the conducted survey in the location indicated that most of the respondents agreed or accepted that the location is feasible for the- A Healing water business, which gained a total of 84% who answered “Yes” and 16% who answered “No.” Therefore, the researchers pursued this location because based on the survey results, the respondents said that the A-Healing Water has possible growth in this location. A-Healing Water is recommended to further expand the business in the location for customers to recognize the business in the selected location. A-Healing water is recommended to continuously reach the expectation of the customer to satisfy them. A-Healing Water is needed to satisfy the customers. Thus, the researchers recommended improving the services and products that will maintain and retain the customers.